2018
DOI: 10.1002/mawe.201700137
|View full text |Cite
|
Sign up to set email alerts
|

Comparative experimental study on the modification of microstructural and mechanical properties of friction stir welded and gas metal arc welded EN AW‐6061 O aluminum alloys by post‐weld heat treatment

Abstract: In this paper, the effects of post‐weld heat treatment on modification of microstructures and mechanical properties of friction stir welded and gas metal arc welded AA6061‐O plates were compared with each other. Gas metal arc welding and friction stir welding were used as the applicable welding processes for AA6061‐O alloys. The applied post‐weld heat treatment consisted of solution heat treatment, followed by water quenching and finally artificial aging. The samples were classified as post‐weld heat treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…In general, for evaluated conditions, the behavior of microhardness profiles shows an increase in the welded joints regions due to annealed condition of the base metals and solid-state deformation effects produced by the FSW process. The base metals displayed average microhardness values of 42 HV for AA6061-O and 56 HV for AA2024-O, which are consistent with the results reported in other works [41,43]. The highest microhardness value (131HV) was obtained in HH-condition welded joints and is located nearly to ZATM of the advancing side (2024-O).…”
Section: Microhardness and Tensile Test Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In general, for evaluated conditions, the behavior of microhardness profiles shows an increase in the welded joints regions due to annealed condition of the base metals and solid-state deformation effects produced by the FSW process. The base metals displayed average microhardness values of 42 HV for AA6061-O and 56 HV for AA2024-O, which are consistent with the results reported in other works [41,43]. The highest microhardness value (131HV) was obtained in HH-condition welded joints and is located nearly to ZATM of the advancing side (2024-O).…”
Section: Microhardness and Tensile Test Resultssupporting
confidence: 89%
“…All fracture regions were located on the AA-6061-O side. For the HH condition, it is probable that the homogenization of the microstructure of both materials in the stir region increased the quantity of AA2024-O in the mixture, slightly increasing the tensile properties of the welded joint compared to the LL conditions [41,43]. Although the probable highest density of dislocations produced by the light-high ratio (ω/v) of LL conditions compared to HH condition could explain the apparent higher observed yield strength in this welded joint [43].…”
Section: Microhardness and Tensile Test Resultsmentioning
confidence: 87%
“…They came to the expected conclusion that better mechanical and fatigue properties were obtained with the FSW method. A similar comparison was also made by Gencer et al [5] and Jannet et al [6], with a similar result to that found by Kuleci.…”
Section: Introductionsupporting
confidence: 89%
“…Wang [7] was able to increase the mechanical properties of welded joints from an initial value of 69% up to 84% of the base material after applying the heat treatment. The UTS value of the joint was 284 MPa and Gencer [5] achieved a joint strength of 83% of the base material after applying T6 heat treatment using the FSW method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation